Impact of Ethnicity on Breast Cancer Outcome: A Systematic Review and Meta-Analysis of Randomized Phase III Trials of the Last Decade - Emma Zattarin; Luca Moscetti; Elisa D'Agostino; Alberto Bertolotti; Isabella Sperduti; Chiara Chiavelli; Fabio Canino; Federico Piacentini; Laura Cortesi; Massimo Dominici; Angela Toss (JCO Global Oncology)
PURPOSEIt remains uncertain whether ethnicity affects the benefit derived from novel breast cancer (BC) treatments. Thus, we conducted a systematic review and meta-analysis to evaluate the heterogeneity of treatment efficacy across different ethnic groups, in both the advanced BC (aBC) setting and the early BC (eBC) setting.METHODSWe systematically searched PubMed, Embase, and Scopus for phase III randomized controlled trials (RCTs) leading to BC drug approval between 2013 and 2023 that had available hazard ratios (HRs) for outcome according to ethnicity. We excluded nonrandomized studies. We compared the three most represented ethnic groups, Whites, Asians, and Blacks, among themselves and with other underrepresented groups (UGs). The pooled HRs and 95% CI in ethnic subgroups were calculated using a random-effects model, and the heterogeneity between the estimates was assessed with an interaction test.RESULTSAmong 23 selected RCTs (14,000 patients) in the aBC setting, 20 provided HRs (95% CI) for progression-free survival (PFS) in the subgroup of Whites, 17 for Asians, four for Blacks, and 23 for non-Asians (Whites + all non-Asian UG) or non-Whites (Asians + all non-Asian UG). Risk of bias was low for all the included RCTs. The HRs for PFS with experimental versus control drugs were 0.62 (95% CI, 0.57 to 0.68) for Whites, 0.54 (95% CI, 0.44 to 0.66) for Asians, and 0.54 (95% CI, 0.34 to 0.85) for Blacks with no significant interethnic difference (P = .233 for Whites v Asians, P = .564 for Whites v Blacks, P = .992 for Asians v Blacks). Similarly, Whites versus non-Whites and Asians versus non-Asians showed no significantly different magnitude of benefit (P = .406 and P = .226, respectively). No differences were observed in eBC trials either.CONCLUSIONThese results offer reassurance for the broader applicability of clinical trial results despite ethnic imbalance.